ASSESSMENT OF THE COMPANIES’ COMPETITIVENESS LEVEL IN CURRENT CONDITIONS - KRAVCHENKO, Olha; CHELOMBITʹKO, Oleh; ZHYLENKO, Andrii; KYCHYHIN, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The aim of the article is to analyze the components of a company’s competitiveness and develop a methodological approach to assessing its achieved level. It is substantiated that competitiveness should be considered from the standpoint of both the competitiveness of the company’s activities and the competitiveness of individual goods (services, works). The main essential characteristics that determine the level of companies’ competitiveness are highlighted, namely: flexibility and adaptability, effective resource management, innovation, and environmental responsibility. The company’s competitive stability is defined as its ability to achieve stable economic development and strengthen market positions in the process of the industry environment evolution. It is proposed to assess the level of a company’s competitive stability based on the analysis of key characteristics, namely: the economic sustainability and the market sustainability of the company. Economic sustainability is defined as a company’s ability to ensure stable growth and efficient use of available resources for long-term functioning in a competitive market environment. Market sustainability of a company is interpreted as its ability to adapt to changes in the market environment and provide competitive advantages in industry markets. It is justified that when assessing and analyzing the achieved level of competitiveness of a company, it is necessary to consider the specified indicators comprehensively. A methodological approach to assessing the achieved level of competitiveness of companies is proposed. It involves collecting information on product demand and analyzing the competitive environment, assessing market prospects, identifying key factors influencing the company’s competitiveness, analyzing the effectiveness of its management system, assessing its investment attractiveness, and analyzing financial stability.